Pathways to Green Growth: Unveiling the Roles of Institutional Quality, Information and Communication Technology Diffusion, and Trade Integration - Hoang, Tri M.; Nguyen, Thanh Phuc; Duong, Trang Thi-Thuy (International Journal of Energy Economics and Policy, 2025)
This study investigates the impacts of institutional quality, Information and Communication Technology (ICT) diffusion, and trade openness on green growth in 21 countries from 2000 to 2019, using FMOLS, DOLS, quantile regression, and Dumitrescu–Hurlin causality tests. Results show that institutional quality consistently and significantly fosters green growth, while ICT diffusion and trade openness impose adverse effects. Efficiency gains from ICT trigger a rebound effect, thus undermining sustainability. Quantile regressions indicate that institutional quality benefits economies at lower quantiles but diminishes at higher ones; ICT negatively affects lower and median quantiles; and trade openness is largely detrimental except at the lowest quantile. Causality analysis reveals unidirectional effects from institutional quality and trade openness to green growth, while ICT and green growth share bidirectional feedback. Overall, policy solutions should strengthen governance, manage ICT rebound effects, and integrate environmental objectives into trade.